O Serviço Social e a reprodução do conservadorismo: análise da atuação profissional na Política de Assistência Social em Aracaju-SE - Moreira, Taira Cris de Jesus (2013)
The study presented here focuses the reproduction of conservatism in Social Work with a focus on ways that conservatism is expressed in the professional practice of social workers linked the Municipal Social Welfare and Citizenship (SEMASC) in Aracaju-SE. To understand the extent to which relationships and rationalities conservative has characterized the field of professional practice of social workers, was adopted as the analytical reference method contained in marxist philosophy. The approach used in this research was predominantly qualitative, while quantitative privilege. The survey sample was non -probabilistic intentional, accessibility, consisting of 23 social workers gazetted. The survey results showed that social workers SEMASC has been unable to perform a satisfactory objective professional intervention in institutions, in order to distance himself from the conservatism that nourishes the logic of the bourgeois order. They also showed that the lack of working conditions of social workers SEMASC for policy implementation is seen in the dismantling of the social assistance network as well as social policies and for this disarticulation, professionals tend to reduce their timely action to meet, the demands of palliative users, which ultimately promotes the maintenance of bourgeois rationality. It was also found that the lack of working conditions and implementation of social welfare policy in Aracaju has impacted on how to contact social workers with the users, since it has been reduced to the attendance of the daily demands of emergency or immediate users. It found the effort and commitment of social workers surveyed with continuing vocational training and permanent, and that they have an understanding of the importance and contribution of academic training for professional practice in order to offer subsidies through the theoretical collection for reflection you can situate the practice. It was concluded that, given the results of the study (field research and literature), social workers surveyed demonstrated clearly the elements that collaborate to a practice that intends to be critical and, indeed, the speech of the majority of these professionals transpires attempt to distance himself from the conservative aspects that marked the genesis of profession. However , it appears that conservatism - as an expression of the bourgeois order ideocultural - remains reproducing within the various spheres of social life in capitalism (social relations , class , state , form of knowledge, institutions , social organizations , social policies) regardless awareness that social workers have about the processes that have determined its reproduction, or in spite of his criticism of conservatism and attempt to break ensured the principles and fundamentals of PEPSS.